Web service based multi-channel application - Neves, P.A.C.S. (2011)
The paper presents an application using a purpose-created web service that is consumed in a multi-channel environment. The service clients span over the common web interface, a JAVA-enabled GSM 2.5G mobile phone, and a Microsoft® Windows® application. The web service provides basic message passing functionality.